1986
DOI: 10.1002/hep.1840060205
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Antibody Synthesis in Patients With Chronic Hepatitis B Infection

Abstract: In vitro synthesis of the anti-HBc, anti-HBs and polyclonal IgG and IgM classes of antibodies were determined from supernatants of peripheral blood mono-nuclear cells cultured in the presence of pokeweed mitogen. Thirty-seven patients with chronic hepatitis B and 10 healthy control subjects whose sera were positive for anti-HBs formed the study group. Twenty-four of 37 patients showed histologic evidence of chronic active hepatitis B while the remaining 13 patients had chronic persistent hepatitis B. Lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…There was no direct cytopathic effects on hepatocytes by HBV infection by the presence of a lot of asymptomatic chronic HBV carriers with no signs of liver injury[42]. Previous studies found defects of the immune response in HBV chronic infected patients, including reduction of HBV-specific antibodies[43, 44], delayed lymphocytes migration, and increment of suppressor lymphocytes[45]. Circulating HBsAg is probably the mechanism of defective immune response in HBV carriers[43, 46].…”
Section: Discussionmentioning
confidence: 99%
“…There was no direct cytopathic effects on hepatocytes by HBV infection by the presence of a lot of asymptomatic chronic HBV carriers with no signs of liver injury[42]. Previous studies found defects of the immune response in HBV chronic infected patients, including reduction of HBV-specific antibodies[43, 44], delayed lymphocytes migration, and increment of suppressor lymphocytes[45]. Circulating HBsAg is probably the mechanism of defective immune response in HBV carriers[43, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients with CPH exhibited significantly higher HBV-DNA levels in sera compared with patients with CAH. IgG synthesis after PWM stimulation was markedly impaired in the CPH group as compared with CAH patients and "healthy" controls ( 187). Similarly, significantly decreased responsiveness of the same lymphocyte population to PWM.…”
Section: Hbsag-induced Antibody Secretion In Vitromentioning
confidence: 85%
“…In most studies in vitro where the capacity of PBL or purified B-cells from patients with chronic liver disease type B to produce anti-HBs after stimulation with PWM (172, [185][186][187] or HBsAg (154,171,186) has been evaluated, anti-HBs has been absent from all carrier lymphocyte supernatants. Polyclonal IgG and IgM, as well as detectable amounts of anti-HBc were, however, produced in most carriers after PWM stimulation (1 72, 185-1 87).…”
Section: Hbsag-induced Antibody Secretion In Vitromentioning
confidence: 99%
“…2 It has been reported that both cellular and humoral immune responses to HBV-related antigens are defective in human HBV carriers [3][4][5][6] and in HBV-transgenic mice. 7 HBV carriers can not produce specific antibody to hepatitis B surface antigen (HBsAg) in vivo and most of these studies in vitro have documented the abnormalities in function of regulatory and helper T cells, and the inability of B cells to produce specific antibody in response to HBsAg.…”
Section: Introductionmentioning
confidence: 99%
“…7 HBV carriers can not produce specific antibody to hepatitis B surface antigen (HBsAg) in vivo and most of these studies in vitro have documented the abnormalities in function of regulatory and helper T cells, and the inability of B cells to produce specific antibody in response to HBsAg. [2][3][4][5][6] On the other hand, some investigators could not detect any substantial defects in the function of T and B lymphocytes in HBV carriers. 8,9 Under such diverse reports about the immune response of HBV carriers on HBV-regulated antigens, it was interesting to elucidate the immune response of HBV carriers to HBV-unrelated antigens to have further insight into the exact immune status of HBV carriers.…”
Section: Introductionmentioning
confidence: 99%